2020
DOI: 10.21776/ub.jitode.2020.008.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Porters’ Rights in Mountain Tourism: Mount Semeru in Bromo Tengger Semeru National Park

Abstract: This study aims to investigate the implementation of rights focusing on the policy and working practices of porters. A total of nine respondents, including two National Park employees, two tour operator representatives, and five porters, participated in the interviews. Data from observation and interviews analyzed through a qualitative descriptive paradigm. Overall interviews revealed that Bromo Tengger Semeru National Park policies have not adequately covered issues on portering activities. Existing policies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A study by Angling (2020) on porters' rights and working practices in mountain tourism revealed that policies have not adequately covered issues on porters' activities. Existing policies are limited to the tariff, guided trekking and organizational aspects of the porters' Association.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Angling (2020) on porters' rights and working practices in mountain tourism revealed that policies have not adequately covered issues on porters' activities. Existing policies are limited to the tariff, guided trekking and organizational aspects of the porters' Association.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Multiple studies conducted by Angling (2020), Barott (2018) and Upasana and Boban (2018) specifically examined the situation of porters in Indonesia and Nepal. However, these studies primarily focused on working conditions and strategies for improvement without delving into the socio-economic welfare implications of such conditions.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation